Domiciliary Cockroaches as Carriers of Human Intestinal Parasites in Lagos Metropolis, Southwest Nigeria: Implications for Public Health - Adedotun A Adenusi; Mary I Akinyemi; Dele Akinsanya (Tehran University of Medical Sciences, 2018)
Background: Domiciliary cockroaches are obnoxious pests of significant medical importance. We investigated the prevalence of human intestinal parasites in cockroaches and its attendant public health importance. Methods: Overall, 749 cockroaches (Periplaneta americana, 509, Blattella germanica, 240) caught by trapping from 120 households comprising 3 different housing types in Somolu, Lagos metropolis, southwest Nigeria, in 2015 were screened for human intestinal parasites using standard parasitological techniques. Results: The prevalence of human intestinal parasites in cockroaches was 96.4%. There was no statistically significant difference (P> 0.05) in parasite prevalences between P. americana (95.7%) and B. germanica (97.9%). Parasite species identified and their prevalence were as follows: Entamoeba histolytica/dispar (44.1%), E. coli (37.8%), Giardia lamblia (18.7%), Cryptosporidium sp. (13.8%), Ascaris lumbricoides (61.3%), Trichuris trichiura (55.8%), hookworms (11.6%), Strongyloides stercoralis (11.7%), Taenia/Echinococcus spp. (10.5%), Enterobius vermicularis (17.2%) and Hymenolepis nana (11.6%). Parasite prevalence and burdens varied with housing type; the prevalence was significantly higher statistically (P< 0.05) in cockroaches from low-cost bungalow, LCB (100%) and low-cost, 2-storey, LC2-S (100%) houses than in medium-cost flats, MCF (81.3%). Parasite burdens were also significantly higher statistically (P< 0.05) in cockroaches from LCB or LC2-S than in cockroaches from MCF. Parasite prevalences between cockroach gut and body surfaces were not statistically significant (P> 0.05) but mean parasite burdens in gut were significantly higher statistically (P< 0.05) than on body surfaces. Conclusion: Cockroaches types carry transmissive stages of human intestinal parasites and may act as reservoirs and potential mechanical vectors for disease transmission.